Chucky. Season one [videorecording (DVD)] - Mancini, Don, 1963- (Universal, 2022)
After teenage loner Jake Webber discovers a vintage 'Good Guy' doll at a suburban yard sale, a quiet American town soon erupts into mayhem as a blood-chilling murder spree begins to spill everyone's deepest and darkest secrets. While Chucky unleashes havoc, familiar faces from his past return and threaten to reveal his shadowy origins as a seemingly ordinary child who somehow became the legendary murderous doll.